Rancang Bangun Sistem Pendukung Keputusan Untuk Kenaikan Jabatan Karyawan Pada PT Masmedia Buana Pustaka Sidoarjo Menggunakan Metode Profile Matching - Aldi Susanto; Jusak Jusak; M.J. Dewiyani Sunarto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Human Resources is the most important thing to create a good work environment in a company, of course having reliable resources is the hope of every company. At PT Masmedia Buana Pustaka Sidoarjo the promotion was carried out manually by only paying attention to the tenure of an employee and with a simple annual performance appraisal, so that the decision making process was still not effective in making decisions. With that, we need a Decision Support System which will be useful for leaders in making decisions by adjusting the criteria and target values expected by the company. Then the application of the method applied is the Profile Matching algorithm. With this method, the user can find out the difference in competence between individual competencies and the competencies expected by the company. PT Masmedia Buana Pustaka Sidoarjo needs an application that is useful in helping make a decision on the placement of employees in a position. So that the results are obtained in the form of a report on the complete calculation of the profile matching algorithm up to the recommendation rating of prospective employees which can later be considered by HRD in the promotion selection process